THE ROLE OF HEALTH DIAGNOSIS ON GYMNASIUM NEEDS OF STUDENTS OF UNIVERSITAS AIRLANGGA, SURABAYA - Ragilia Indah Lutfiana (The Indonesian Journal of Public Health, 2020)
Fitness center / gymnasium is one of the sports favored by the public because in the fitness center has a range of tools and facilities that have been designed so that it can be used as a tool for physical exercise that right. So the longer the gymnasium has also become a necessity for people, Necessity (need) here are divided into two categories, felt or perceived (subject assessment) and evaluated (clinical diagnosis).This study uses a quantitative approach. While the survey research techniques are activities taking samples from a population and using questionnaires as the main data collection tool to understand the needs of students related Airlangga University gymnasium. The results of the study that students need a gymnasium facilities are only accessible by only academy person and in which there is a pool and a cafeteria. This may indicate that students are given follow the advice of doctors to perform the sport swim and is in accordance with the desired exercise by students.